Studi Deskriptif Dimensi Pengetahuan, Level Kognitif, dan Jenjang Afektif Butir Soal Ujian Sekolah Mata Pelajaran IPS SD Kota Bengkulu Tahun Pelajaran 2021/2022 - Yusnia, Yusnia (UNIB Press, 2022)
This study aims to describe the proportion of the dimensions of knowledge, cognitive level, and affective level about the social studies subject school exam questions for Grade VI Elementary School students in Bengkulu City in the 2021/2022 academic year. This type of research is descriptive research. The object of this research is the grid, questions, and answer keys for school exam questions. The instrument in this study is documentation, including an analysis sheet of the proportion of knowledge dimensions, cognitive levels, and affective levels of school exam questions. The research data in the form of the proportion of the dimensions of knowledge, cognitive level, and affective level were analyzed and then calculated the percentage. The results showed: 1) the proportion of knowledge dimensions, including factual is 29 items (82.86%) and conceptual is 6 items (17.14%); 2) the proportion of cognitive levels, Level 1 (LOTS) is 3 items (8.57%), Level 2 (MOTS) is 11 items (31.43%), and Level 3 (HOTS) is 21 items (60 %); 3) the proportion of affective levels, including responding (A2) is 1 item (2.86%), appreciating (A3) is 7 items (20%), organizing (A4) is 2 items (5.71%) , and characterization by value (A5) is 1 item (2.86%)